Prognostic and clinicopathological significance of TLR4 expression in patients with breast cancer: a meta-analysis - Wen, Jinxu; Zhang, Jiayi; Wu, Xiaoyong; Yan, Xuemin; Qin, Xiaoru; Wang, Yuexin (Frontiers in Oncology, 2024)
Background: The prognostic value of Toll-like receptor 4 (TLR4) in breast cancer remains to be determined. Therefore, this paper aims to conduct a meta-analysis to assess the correlation between TLR4 and clinicopathological indicators as well as survival outcomes in breast cancer. Method: Related literature retrieved from Embase, PubMed, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI) and China Wanfang.The search deadline is April 12, 2023. The outcome measures employed in the study comprised hazard ratio (HR), odds ratio (OR), and 95% confidence interval (CI) as effective indices. The data analysis was conducted using Stata 17.0 software. Results: High TLR4 expression was associated with lymph node metastasis (OR=2.077, 95%CI=1.160-3.717, P= 0.014), tumor size (≥2 cm) (OR=2.194 , 95%CI= 1.398-3.445, P= 0.001), PR expression (OR = 0.700, 95% CI = 0.505–0.971, P= 0.033 ), and clinical stage (OR = 3.578, 95%CI= 3.578-5.817, P＜0.05), but not with histological grade (95%CI= 0.976-1.735, P= 0.072), ER expression (OR = 1.125, 95% CI = 0.492–2.571,P= 0.781), and HER-2 status (OR = 1.241, 95% CI = 0.733–2.101, P = 0.422). In addition, TLR4 overexpression was an independent prognostic indicator of DFS (HR= 1.480, 95%CI= 1.028- 2.130, p= 0.035) in breast cancer patients, but not related to OS(HR=1.730, 95%CI= 0.979-3.057, P= 0.059). Conclusions: From our main analysis results, high TLR4 expression is associated with lymph node metastasis, larger tumour size (≥2 cm), later clinical stage, negative PR expression and shorter DFS, suggesting poor prognosis in breast cancer patients.